2015
DOI: 10.1371/journal.pone.0122727
|View full text |Cite
|
Sign up to set email alerts
|

In the Early Stages of Diabetes, Rat Retinal Mitochondria Undergo Mild Uncoupling due to UCP2 Activity

Abstract: In order to maintain high transmembrane ionic gradients, retinal tissues require a large amount of energy probably provided by a high rate of both, glycolysis and oxidative phosphorylation. However, little information exists on retinal mitochondrial efficiency. We analyzed the retinal mitochondrial activity in ex vivo retinas and in isolated mitochondria from normal rat retina and from short-term streptozotocin-diabetic rats. In normal ex vivo retinas, increasing glucose concentrations from 5.6mM to 30mM cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Previous studies demonstrated that five isoforms of UCPs are expressed in bovine retinal microvascular endothelial cells and pericytes. UCP1, UCP2, and MnSOD were shown to be expressed in high-glucose environment [ 82 ]. Retinal neuron apoptosis in DR was observed and shown to be associated with a decrease in MnSOD expression [ 83 , 84 ].…”
Section: Mitochondrial Dysfunction Roles In the Dr Pathogenesismentioning
confidence: 99%
“…Previous studies demonstrated that five isoforms of UCPs are expressed in bovine retinal microvascular endothelial cells and pericytes. UCP1, UCP2, and MnSOD were shown to be expressed in high-glucose environment [ 82 ]. Retinal neuron apoptosis in DR was observed and shown to be associated with a decrease in MnSOD expression [ 83 , 84 ].…”
Section: Mitochondrial Dysfunction Roles In the Dr Pathogenesismentioning
confidence: 99%
“…A recent report suggests that short‐term diabetes induces mitochondrial activity maintenance through prevention of oxidative stress and not dysfunction (Osorio‐Paz et al . ). Therefore, it is reasonable to postulate that reducing the amount of potentially damaging molecules through pharmacological inhibition could benefit diabetic retinal function and mitigate DR progression in the absence of mitochondrial dysfunction and mtDNA damage.…”
Section: Discussionmentioning
confidence: 97%
“…These results are similar to a previous demonstration of protective, positively adaptive mitochondrial protein activity changes in response to short‐term diabetes (Osorio‐Paz et al . ), which results in decreased mitochondrial efficiency but not dysfunction. Base and location specific quantitative assessment of retinal mtDNA damage in the form of somatic deletions and mutations across multiple high‐depth mitochondrial sequencing datasets demonstrate that no induction of deletions or mutations occurs with early diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…UCP1 is a potential target for the treatment of patients with diabetes and improves the whole metabolism . In addition, the altered expression of UCP2 is implicated in the pathogenesis of diabetes, and the activation of UCP2 in diabetic mitochondria seems to be a response to the diabetes process that leads to more efficient cleaving of ROS . Of interest, the upregulation of UCPs has been observed in several MR models, indicating a potential mechanism in MR‐mediated mitochondrial respiratory chain.…”
Section: Mr and Diabetesmentioning
confidence: 99%
“…[63] In addition, the altered expression of UCP2 is implicated in the pathogenesis of diabetes, [64] and the activation of UCP2 in diabetic mitochondria seems to be a response to the diabetes process that leads to more efficient cleaving of ROS. [65,66] Of interest, the upregulation of UCPs has been observed in several MR models, [67,68] indicating a potential mechanism in MRmediated mitochondrial respiratory chain. For example, renal gene expression of the mitochondrial UCP1 is upregulated in MR-fed animals, [42] and it has been demonstrated to be an essential mediator of the effects of MR on energy expenditure and metabolism.…”
Section: Oxidative Stressmentioning
confidence: 99%